2021
DOI: 10.1021/acs.inorgchem.1c02961
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Mediated Transmetalation as a Route to Anionic N-Heterocyclic Olefin Complexes in the p-Block

Abstract: Anionic N-heterocyclic olefins (aNHOs) are suited well for the stabilization of low-coordinate inorganic complexes, due to their steric tunability and strong σand π-electron donating abilities. In this study, the new two-coordinate zinc complex ( Me IPrCH) 2 Zn ( Me IPrCH = [(MeCNDipp) 2 CCH] − , Dipp = 2,6diisopropylphenyl) is shown to participate in a broad range of metathesis reactions with main group element-based halides and hydrides. In the case of the group 14 halides, Cl 2 E•dioxane (E = Ge and Sn), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 97 publications
2
13
0
Order By: Relevance
“…Given the synthetic potential of a transmetalation reaction, we decided to carefully study this synthetic route, evaluate its scope for another ligand system, and further explore the transmetalation chemistry between two main-group elements or a main-group element and a transition metal. A further impetus comes from recent transmetalation chemistry by the groups of Jones, Zeckert, Beckmann, Roesky, and others. Herein, we describe the synthesis and characterization of a tin­(II) compound ( 2 ) based on a nacnac framework with a picolyl side arm. Subsequently, we have shown 2 undergoes smooth transmetalation with Ni to generate analogous Ni complex ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the synthetic potential of a transmetalation reaction, we decided to carefully study this synthetic route, evaluate its scope for another ligand system, and further explore the transmetalation chemistry between two main-group elements or a main-group element and a transition metal. A further impetus comes from recent transmetalation chemistry by the groups of Jones, Zeckert, Beckmann, Roesky, and others. Herein, we describe the synthesis and characterization of a tin­(II) compound ( 2 ) based on a nacnac framework with a picolyl side arm. Subsequently, we have shown 2 undergoes smooth transmetalation with Ni to generate analogous Ni complex ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…a second equivalent of the NHO used), proceed via direct halosilane elimination of a preformed silylated NHO or via salt metathesis whereas in the herein reported example no byproducts are formed. 20,21 Here we demonstrate the direct formation of this ligand class in the coordination sphere of titanium by formal intramolecular proton transfer to one pentafulvene ligand. Although in principal there is a second pentafulvene ligand to potentially react with, no second C–H activation occurs regardless of the stoichiometry used for this reaction.…”
Section: Resultsmentioning
confidence: 71%
“…This has been exploited first by Rivard and coworkers, and later by Ghadwal et al , and more recently again the Rivard group reported stable and base-free divinylgermanes, divinylgermylenes, and expanded this protocol to a series of homoleptic tetrylenes and a zinc complex. 20 To date, all reported examples of compounds bearing the anionic N-heterocyclic vinyl ligand require either stoichiometric amounts of an external base ( e.g. a second equivalent of the NHO used), proceed via direct halosilane elimination of a preformed silylated NHO or via salt metathesis whereas in the herein reported example no byproducts are formed.…”
Section: Resultsmentioning
confidence: 78%
“…To our knowledge, there are only two examples of aNHO‐transition metal complexes. One example was reported by our group, wherein two aNHO ligands are bound to a Zn(II) center yielding a linear two‐coordinate species ( E , Chart 1) [8a] . The second very recent example by Beckhaus is the aNHO complex F , obtained from the reaction of an NHO with a bis(π‐η 5 :σ‐η 1 ‐pentafulvene)titanium precursor (Chart 1) [8b]…”
Section: Introductionmentioning
confidence: 99%
“…Given our recent report of the lithiated aNHO ( Me IPrCH)Li ( Me IPrCH=[(MeCNDipp) 2 C=CH] − ; Dipp=2,6‐ i Pr 2 C 6 H 3 ), and its ability to form main group element complexes by salt metathesis [8a,17] low‐coordinate Group 4 metal complexes supported by anionic N ‐heterocyclic olefins were selected as synthetic targets in this study.…”
Section: Introductionmentioning
confidence: 99%